ENHANCING HALAL PROCUREMENT PRACTICE AMONG HOTEL IN MALAYSIA - Shari, Sara Shakira Binti; Moid, Muzairihana Binti Mohd; Supian, Kamisah Binti; Suhaimi, Anora Shaliaty Binti (International Journal of Business and Management Future, 2021)
The demand for halal products has increased significantly throughout the world, either from Muslims themselves or non-Muslim communities. This phenomenon is due to an increasing concern for health as they believe that halal food has better cleanliness and safety. Few studies have shown that the supply chain plays a crucial role in ensuring that the products are halal compliant and that procurement is one of the main branches. In the hotel industry, the procurement department is responsible for ensuring that raw materials are arranged, purchased, delivered, and consumed effectively. Transparency, supplier engagement, and risk management are three elements that are highlighted matters in the hotel industry. Previous studies have shown that these three elements have a significant role in enhancing procurement practice in organisations. This paper focuses on the elements and effectiveness of halal procurement practises among Malaysian hotels. This study also aims to help companies evaluate their halal procurement practises and develop effective strategies to ensure that food products follow halal guidelines that ultimately enhance business performance.